Development I Standardization of “Coldmaster” Granules (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
A technology has been developed for producing granules from dry plant extract "Coldmaster." The resulting granules are standardized according to the main biologically active substances: flavonoids, glycyrrhizic acid, ascorbic acid; installed numerical indicators of granules. Quality control methods have been developed, on the basis of which a draft Pharmacopoeial monograph for the Coldmaster Granules enterprise was compiled.